THE EXPERIENCE OF INTRALESIONAL BLEOMYCIN FOR ORBITAL VASCULAR ANOMALIES - Kamil, Zeeshan; Qirat Qurban; Muhammad Tanweer Hassan Khan (Journal of Ayub Medical College Abbottabad, 2021)
P Background: Orbital vascular anomalies are congenital and pose a challenge. They require various treatment modalities which are often unsuccessful. The use of intralesional Bleomycin has gained popularity in recent times as a scar less procedure when other treatment modalities are not effective. Purpose: To share the experience of using intra lesional Bleomycin in orbital vascular anomalies in a Tertiary care hospital. Methods: This quasi-experimental study was carried out at Layton Rahmatullah Benevolent Trust (LRBT) Teaching Tertiary care hospital, Karachi from 1st June to 31st December 2018. It included fifteen patients of various orbital vascular anomalies treated with injection of intra lesional sclerosing (Bleomycin) agent. Patients were given multiple injections and the effects of sclerosing agent on orbital vascular anomalies were observed. Results: Results were excellent in terms of regression of vascular anomalies. Conclusion: Intralesional sclerosing agent (Bleomycin) has an outstanding role in vascular tumour.